Development of specimen mounting and gripping system for planar biaxial tensile testing of biological membrane tissue - Siddiqui, Aashir (Department of Mechanical Engineering, 2025)
There has always been a need to understand the mechanical properties of biological membrane tissues in the fields of medicine, biomechanical engineering, and cosmetology. These tissues are known to display complex anisotropic, hyperelastic, and non-linear stress-strain properties, while also being sensitive to environmental conditions. Given these complexities, ongoing efforts are being made to develop a suitable testing methodology. At the University of Cape Town, the Blast Impact and Survivability Research Unit is building a testing methodology (using their in-house planar biaxial tensile testing and bulge inflation devices) that has thus far been used to test small intestine submucosa tissue. As part of this ongoing effort, this research aimed to build a tissue-gripping system that can be used to attach a specimen to the planar biaxial tensile testing machine since the previous clamping method was not suitable. A rake clamping system that allowed contra-lateral motion was built, along with the necessary tooling to attach the rakes and excise a square-shaped specimen. Planar biaxial tensile tests were then conducted on small intestine submucosa tissue to assess the performance of these rakes. The rakes were found to be effective at allowing the tissue to expand and contract contra-laterally while also being structurally sound enough to withstand the loads applied during testing. In the progression of this research, improvements were also made to the optical deformation measurements and sample thickness measurements. Regarding the optical deformation measurements, it was found that speckling the sample with multi-coloured paints improved correlation, and the addition of Cross Polarising Line filters removed harsh reflections that would stop the Digital Image Correlation software from evaluating facet displacement. Looking at the thickness measurements, a migration was made from wax histology to cryo-histology for preparing sections to measure the samples' thickness. Images taken showed that the cryo-sectioned tissue had undergone less dilation and fibre fraying than the wax histology used by prior students, offering more realistic and accurate thickness measurements. The successes found with the designed rakes and the improvements made to the testing methodology have laid the groundwork for other biological tissues to be tested.